2002
DOI: 10.1210/er.2001-5002
|View full text |Cite
|
Sign up to set email alerts
|

V. Meta-Analysis of the Efficacy of Hormone Replacement Therapy in Treating and Preventing Osteoporosis in Postmenopausal Women

Abstract: HRT has a consistent, favorable and large effect on bone density at all sites. The data show a nonsignificant trend toward a reduced incidence in vertebral and nonvertebral fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
317
0
16

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 494 publications
(348 citation statements)
references
References 77 publications
15
317
0
16
Order By: Relevance
“…In the present study, use of ERT was associated with a lower concentration of a marker for bone collagen (PINP) synthesis compared with controls. This has been shown by others (58). The higher BMD in ERT users in the present study might be explained by an increase in the synthesis of mature bone collagen tissue, even though ERT seems to reduce the synthesis of new collagen molecules (indicated by lower s-PINP).…”
Section: Bone Turnover and Bmdsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, use of ERT was associated with a lower concentration of a marker for bone collagen (PINP) synthesis compared with controls. This has been shown by others (58). The higher BMD in ERT users in the present study might be explained by an increase in the synthesis of mature bone collagen tissue, even though ERT seems to reduce the synthesis of new collagen molecules (indicated by lower s-PINP).…”
Section: Bone Turnover and Bmdsupporting
confidence: 81%
“…Bone mass density (BMD) decreases by age, especially after menopause, whereas tendon crosssectional area (CSA) is greater in postmenopausal women compared with young women (35). In postmenopausal women, estrogen replacement therapy (ERT) preserves bone mass (58), and the presence of estrogen, estrogen receptors, and mechanical loading has synergistic positive effects on bone mass (9,55). The effect of combined ERT and physical training on tendons is elusive.…”
mentioning
confidence: 99%
“…Several studies from the 1970s reported that treatment with estrogen alone or estrogen plus progestogen at the time of menopause prevented accelerated bone loss (9,10). According to a meta-analysis published in 2002, preparations of estrogen with or without progestogen were significantly more effective than placebo in preserving and increasing BMD (11). Several follow-up studies demonstrated that discontinuation of estrogen therapy caused bone loss similar to that seen in early menopause (24).…”
Section: Ovx Ert Ovx E+p Rtmentioning
confidence: 99%
“…Clinical trials evaluating the changes of bone microarchitecture during postmenopausal osteoporosis and the effects of therapuetic agents on these changes are needed. The hormone replacement therapy (HRT) is known to prevent accelerated bone loss (9,10) and improve bone mass in postmenopausal osteoporosis (11). In addition to improvement in BMD, fractures were decreased with hormone therapy (12).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen replacement therapy reduces bone resorption by decreasing serum levels of osteoclast-stimulating cytokines and up-regulating transforming growth factor beta, which inhibits bone resorption by decreasing the activity of osteoclasts and increasing their apoptosis. [2] Estrogen prevents postmenopausal bone loss, improves bone density, [3][4][5][6][7] reduces the incidence of vertebral fractures in postmenopausal women 472…”
Section: Introductionmentioning
confidence: 99%